Analysis of the Needs of the Adab Education Program for Drug Rehabilitation Institutions - Muhammad Abdul Jabar; Wido Supraha; Imas Kania Rahman (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
At this time, there are many people who had cured from drugs addiction, re-consuming drugs. Jail or residential drug treatment do not stop them re-consuming drugs. Research argues that courtesy education program is important to be implemented in residential drug treatment. Therefore, this research aimed to analyze the need of courtesy education program at residential drug treatment. The method that is used in this research is library research. Library research is a method of collecting data from documents, books, theories, and so on. Furthermore, objective of this research is focused on analyze need of courtesy education program at residential drug treatment.